Developing Interactive Teaching Materials using Nearpod to Strengthen Students’ Mathematical Literacy - Septy Sari Yukans; Rahma Siska Utari; Dea Alvionita Azka; Dinda Audina Rahmah (FKIP Universitas PGRI Palembang, 2025)
The low achievement of Indonesian students in international assessments such as the Programme for International Student Assessment (PISA) highlights the need for contextual and technology-based innovations in mathematics learning. This study aims to develop Nearpod-based interactive teaching materials that are valid, practical, and have a potential effect in strengthening junior high school students’ mathematical literacy. The research employed a formative evaluation approach consisting of the stages of preliminary study, self-evaluation, expert review, one-to-one, small group, and field test. The participants were 31 eighth-grade students from MTsN 1 Ogan Ilir, South Sumatra. Data were collected through walkthroughs, interviews, observations, and questionnaires, and analyzed using a qualitative descriptive method. The findings revealed that the developed teaching materials were valid in terms of content, construct, and language; practical for classroom implementation; and demonstrated a potential effect in enhancing students’ mathematical literacy through active engagement in the Formulate, Employ, and Interpret processes as outlined in the PISA 2022 framework. This result from students’ post-test work, which showed improved accuracy in modeling and interpreting the contextual problem. This study contributes a structured and literacy-oriented model for developing technology-based interactive teaching materials, which can serve as a reference for mathematics learning innovation in the 21st century.